Topological Shape Optimization Design of the Whole Bead of 265/35R18 Steel-Belted Radial Tire - Li, Yong; Zhang, Shuang; Wang, Tao; Zhang, Kai; Chen, Long; Han, Shanling (Journal of Research Updates in Polymer Science, 2023)
The tire bead, as the most important load-bearing component at the bead area, is closely related to the durability of the tire, but its structure is developing slowly. For this reason, the topological whole bead design was proposed, although it performs well, many defects existed due to the design based on traditional experience. Therefore, this paper studies the topology shape optimization algorithm, delves into the main criterion based on von Mises and the interlaminar shear stress, and provides guidance for the structurally optimal design of the 265/35R18 radial tire whole bead. The finite element simulation results show that the von Mises of the inner end of the chafer and the end of the carcass cord are reduced by 14.48% and 24.12%, respectively. The interlaminar shear stress decreased by 28.96% and 49.51%, respectively. The von Mises of chafer and carcass cord decreased by 13.17% to 40.36% and 7.71% to 20.51%, respectively. The optimization design is of great significance to further improve the safety performance of tires.